FUNCTIONAL OUTCOME OF BRISTOW-LATARJET PROCEDURE IN POST-TRAUMATIC RECURRENT ANTERIOR SHOULDER INSTABILITY - Haseeb Saqlain Bajwa,; Uddin, Shuja; Zia Uddin,; Hafiz M. Umar,; Rizwan Ul Haq,; Ahmed Umair Asad Khan, (Journal of Ayub Medical College Abbottabad, 2023)
Background: Due to its lack of bony support, the shoulder joint has the broadest range of motion out of all the joints in the body. Instead, one of the joints that dislocate most frequently is the shoulder joint. Multiple pathologic abnormalities, including the traumatic separation of the anterior-inferior capsule-labral complex from the glenoid rim, are caused by repeated anterior glenohumeral dislocation. The objective of the study is to ascertain the Bristow-LATARJET procedure's efficacy in situations of recurrent post-traumatic anterior shoulder instability. Methods: From 31 January 2020 to 31 July 2020, a descriptive case series was undertaken in the orthopaedic surgery department of the Lahore General Hospital. For this study, 71 patients who met the inclusion and exclusion criteria were recruited, and all interventions were conducted while the patients were lying in a beach chair while under general anaesthesia. The Delto-pectoral incision surgical technique was applied. For 12 weeks, all patients underwent clinical follow-up, and the results were documented. Results: There were 50(70.4%) males and 21(29.6%) females in this study & the mean age of the patients were 34.64±10.73. There were 37(52.1%) patients among them the outcome of treatment (Rowe Scale at 12th week) was excellent, among 21(29.6%) it was good, among 8(11.3%) it was fair and among 5 (7.0%) it was poor. There was a significant association between the outcome of treatment (Rowe scale at 12th week) and age groups (p-value: 0.000). Conclusion: The Bristow-LATARJET procedure is deemed to be a very productive, safe, and problem-free procedure for curing post-traumatic reoccurring traumatic anterior shoulder instability